Effect of Risk Based Bank Rating on Financial Performance of Sharia Commercial Banks - Diah Munawaroh; Peny Cahaya Azwari (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
Risk Based Bank Rating (RBBR) is one of the assessments of the new health level of the bank in lieu of CAMELS in accordance in Bank Indonesia Regulation No. 13/1 / PBI / 2011. This study aims to examine the effect of Risk-Based Bank Ratings (Risk Profile, Good Corporate Governance, Earning and Capital) on Financial Performance (ROA). The method used is descriptive statistics, determination of regression models, classic assumption tests, multiple linear regression methods and hypothesis testing. The type of data in this study uses panel data. Based on the results of the study indicate that the ratio of NPF, GCG and CAR does not significantly influence ROA. While the ratio of FDR, BOPO and NOM has a significant effect on ROA.